2020
DOI: 10.1029/2019jd031538
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Gigantic Jet in Southern China: Morphology, Meteorology, Storm Evolution, Lightning, and Narrow Bipolar Events

Abstract: At about 22:43:30 BJT (Beijing Time = UTC + 8) on 13 August 2016, two amateur astronomers in Shikengkong, Guangdong province, and Jiahe County, Hunan province, respectively, fortuitously captured a gigantic jet (GJ) event simultaneously, and the GJ exact location could be triangulated. The parent thunderstorm was in a very humid environment (Precipitable Water [PWAT] in excess of 60 mm), featuring high convective available potential energy (CAPE of 2,428 J/kg). The GJ occurred in the region with the coldest cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Halos are caused by both positive and negative CG lightning (Williams et al., 2007, 2012; Yang et al., 2018). Blue jets and gigantic jets shoot upwards from cloud tops to the stratosphere, or even to the ionosphere (e.g., Mishin & Milikh, 2008; Pasko, 2008; Yang et al., 2020). They are associated rather with the dynamics and intensity of charge separation in the thundercloud, which determine the energy of intra‐cloud discharges, for example, narrow bipolar events (Chou et al., 2018; F. Liu et al., 2021; Tilles et al., 2019), leading to the formation of these emissions near the cloud tops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halos are caused by both positive and negative CG lightning (Williams et al., 2007, 2012; Yang et al., 2018). Blue jets and gigantic jets shoot upwards from cloud tops to the stratosphere, or even to the ionosphere (e.g., Mishin & Milikh, 2008; Pasko, 2008; Yang et al., 2020). They are associated rather with the dynamics and intensity of charge separation in the thundercloud, which determine the energy of intra‐cloud discharges, for example, narrow bipolar events (Chou et al., 2018; F. Liu et al., 2021; Tilles et al., 2019), leading to the formation of these emissions near the cloud tops.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on the physical features of TLEs and their association with thunderstorms and lightning discharges has focused on individual cases (e.g., Chou et al., 2011; Sato et al., 2016; van der Velde et al., 2006; Yang et al., 2020), which always show their specificities and making it difficult to learn their climatology. The studies of TLEs and related thunderstorms over different regions from ground‐based observation campaigns conducted over several years, like that over the Eastern Mediterranean in winter (Yair et al., 2015), above Europe and parts of the Mediterranean Sea (Arnone et al., 2020), revealed that the climatology of TLEs and lightning varies with geography.…”
Section: Introductionmentioning
confidence: 99%
“…Our results emphasize the importance of convection phase on the initiation of cloud top discharges. Negative NBEs occur as the onset of blue discharges 21 , and positive NBEs serve as the initial stages of gigantic jets 53,54,55 . The competition of NBEs polarities in our findings suggests that the height variations of the upper positive charge layer induced by the strength of updrafts would play a significant role in the initiation of different types of cloud top discharges.…”
Section: Implications For the Initiation Of Cloud Top Discharges Kreh...mentioning
confidence: 99%
“…Since the summer season of (Chen et al, 2014), the amateurs in China, including some professional photographers, have been enthusiastically contributing to the research of TLEs, either by providing the critical observations (e.g., Chou et al, 2016;Yang et al, 2020), or arousing the attention from the publicity. Yang et al (2020) reported the analysis of a gigantic jet event captured by two amateurs concurrently from different sites in southern part of China.…”
Section: Contributions From Chinese Amateursmentioning
confidence: 99%